Control of Essential Commodities Act, 1956 : containing black marketing, anti-hoarding, smuggling, profiteering, gold control, and other control orders - Bangladesh; Mohsin, I. M. M. (Dhaka : Universal Books : Available at Book Syndicate, 1991)
Includes related acts, ordinance, and orders.
Prefatory matter in English and Bengali.
Keywords: Strategic materials -- Law and legislation -- Bangladesh; Food law and legislation -- Bangladesh; Feeds -- Law and legislation -- Bangladesh; Smuggling -- Bangladesh; Profiteering -- Bangladesh; Black market -- Bangladesh; Law